Detecting Socially Desirable Responses In Personality Inventory - Govindasamy, Priyalatha (2011)
This study attempted to detect the socially desirable responses within differential responses. Besides, this study also examined items and personality dimensions that are vulnerable to social desirability. In the experimental design, a sample of 521 students was tested twice with the International Personality Item Pool (IPIP) under honest and socially desirable instructions. Responses from the first administration were classified as honest group responses and those from the second administration were grouped as socially desirable responses. The mean dispersion and fit analysis were applied in detecting socially desirable responses.